SISTEM INFORMASI SIMPAN PINJAM DI KOPERASI SERBA USAHA CILENGKRANG BANDUNG - Suwinarno Nadjamuddin (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2013)
At Cooperative Multipurpose Business Cilengkrang Bandung there are problems of the data management system in use today is still manually using MS applications. Excel as an application program to help save, calculate, analyze and present data. The purpose of this study was to determine the current system, making the design, and testing for Desktop-based Cooperative Information Systems in Cooperative Multipurpose Business Cilengkrang Bandung.The research method used descriptive and action. While the method used is a structured approach and method of using the prototype development. Data collection methods used were observation, interview and documentation. The tools used are Flowmap, Context Diagram, Data Flow Diagrams (DFD), data dictionary and data base design using normalization and table relationships. Software design process using programming languages PHP and MYSQL database, with tools Dreamweaver 8 and apache server.From the research that has been conducted by the author, the Desktop-based Cooperative Information Systems at Cooperative Multipurpose Business Cilengkrang Banfung expected to assist and facilitate cooperative officials in conducting cooperative savings and loans in covering registration, deposits and loans.